A comparative library review of teaching practice and supervision practice between Malaysia and Australia - Keng, Chew Wai; Jusoh, Ahmad Jazimin; Mohd Nor, Mariyati (Journal of Research, Policy & Practice of Teachers and Teacher Education, 2017)
Teaching practice in Malaysia, also known as placement in Australia, is an essential “bridge” that connects theory and skills that student teachers learnt in the university to the real school context. Supervision is a powerful and important supportive mechanism to maximise the outcome of teaching practice. This paper aims to study the differences of teaching practice between Malaysia and Australia. Further, the differences of supervision practice between both countries is also been identified. The research methodology used for this study is library research on Malaysia and Australia teaching and supervision practices. Criteria of the supervision assessment that are implemented in Malaysia and Australia is compared to identify the gap between both countries on supervision practice. The purposes of teaching practice and supervision practice in both countries are discussed.